2021
DOI: 10.1186/s12884-021-03698-5
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcomes in women after controlled ovarian stimulation with gonadotropin releasing hormone agonist long protocol: fresh versus frozen embryo transfer

Abstract: Background Along with progress in embryo cryopreservation, especially the vitrification, freeze all strategy has become more acceptable than ever. Some studies have found comparable or higher live birth rate with frozen embryo transfer (FET) than with fresh embryo transfer(ET)in gonadotropin releasing hormone antagonist (GnRH-ant) protocol. However from our literature research, there have been no reports about live birth rate comparison between fresh ET and FET with gonadotropin releasing hormo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In addition, Liu et al revealed that FET is better than fresh ET in the GnRH antagonist cycle in women with 3-10 oocytes retrieved [23]. However, FET was associated with lower implantation rate and live birth rate in infertile patients who underwent the GnRHa long protocol compared to fresh ET [24]. The patients recruited in the above-mentioned studies were transferred with high-quality cleavage embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al revealed that FET is better than fresh ET in the GnRH antagonist cycle in women with 3-10 oocytes retrieved [23]. However, FET was associated with lower implantation rate and live birth rate in infertile patients who underwent the GnRHa long protocol compared to fresh ET [24]. The patients recruited in the above-mentioned studies were transferred with high-quality cleavage embryos.…”
Section: Discussionmentioning
confidence: 99%